Effect of limited water supply on Melilotus officinalis nutrient content - Kostopoulou P.; Karatassiou M.; Barbayannis N. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The aim of the present study was to investigate the influence of limited water supply on nutrient accumulation of Melilotus officinalis tissues. For this purpose a pot experiment was conducted, where half of the pots were fully irrigated (up to field capacity) and the rest were irrigated with half the quantity of water. Irrigation plan was applied for five weeks during the growing season. At the end of the experiment, randomly selected plant material, divided in roots, shoots and leaves, was dried and the content of K, Na, Mg, Ca, Cu, Fe, Zn and Mn was determined. The results showed that the limited water supply interacted with the mineral content of M. officinalis plants, increasing the concentration of K, Ca, Mg, Cu, Fe and Mn in the leaf tissues. Accumulation of these nutrients could serve as a means to alleviate the adverse impact of drought on important metabolic processes, enhancing M. officinalis tolerance to water stress.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)